Convenient Monitoring System of Intracellular microRNA Expression during Adipogenesis via Mechanical Stimulus‐Induced Exocytosis of Lipovesicular miRNA Beacon. Issue 5 (27th December 2017) - Han, Seungmin; Kang, Byunghoon; Jang, Eunji; Ki, Jisun; Kim, Eunjung; Jeong, Mun‐Young; Huh, Yong‐Min; Son, Hye‐Young; Haam, Seungjoo
Abstract: Noninvasive investigation of microRNAs (miRNAs) expression, which is deeply related to biological phenomena such as stem cell differentiation, in culture soup is particularly useful for monitoring of stem cell differentiation without phototoxicity of living cells, especially when cell morphologies remain unchanged during differentiation. However, real‐time detection of miRNA in culture soup is not recommended because of insufficient miRNA amounts in culture soup. In this study, a convenient method is introduced for real‐time assessing intracellular miRNA in culture soup by using lipovesicular miRNA beacon (Lipo‐mB) and mechanical stimulus‐mediated exocytosis. Pipetting‐harvest of culture soup induces exocytosis‐secretion of fluorescence signal of Lipo‐mB from cytoplasm into culture soup. To demonstrate this method, Lipo‐mB is applied for monitoring of adipogenesis by analyzing the expression levels of various intracellular miRNAs, which are related to adipogenesis regulators. The fluorescence intensity profile of the culture soup is correlated with the quantitative reverse‐transcription‐polymerase chain reaction data and absorbance of Oil Red O staining. These results demonstrate that Lipo‐mB can successfully monitor stem cell differentiation by sensing changes in miRNA expression from culture soup of living cells. Lipo‐mB can be further developed as an accurate sensing system for analyzing subtle differences in genotype, even when changes in phenotype cannot be observed. Abstract : Convenient method for monitoring of intracellular microRNA (miRNA) expression level from culture soup . Lipovesicular miRNA beacon‐nanoplatform senses target miRNA in cytoplasm, and then it is secreted into culture soup by mechanical stimulus‐mediated exocytosis, which is pipetting‐harvest. The system can monitor stem cell differentiation from culture soup without phototoxicity on living cells and cellular fixation step.